2008
DOI: 10.1038/sj.ijo.0803781
|View full text |Cite
|
Sign up to set email alerts
|

The effects of high-intensity intermittent exercise training on fat loss and fasting insulin levels of young women

Abstract: Objective: To determine the effects of a 15-week high-intensity intermittent exercise (HIIE) program on subcutaneous and trunk fat and insulin resistance of young women. Design and procedures: Subjects were randomly assigned to one of the three groups: HIIE (n ¼ 15), steady-state exercise (SSE; n ¼ 15) or control (CONT; n ¼ 15). HIIE and SSE groups underwent a 15-week exercise intervention. Subjects: Forty-five women with a mean BMI of 23.2 ± 2.0 kg m À2 and age of 20.2 ± 2.0 years. Results: Both exercise grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

36
411
6
46

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 426 publications
(499 citation statements)
references
References 41 publications
36
411
6
46
Order By: Relevance
“…Furthermore, we demonstrated that EPOC is significantly greater following 10 min of REHIT compared to 30 min of moderate intensity aerobic exercise. These findings are of importance as several previous studies have observed reductions in fat mass following HIT with some evidence for superior reductions compared with traditional aerobic training (Whyte et al 2010;Gillen et al 2013;Heydari et al 2012;Trapp et al 2008). Since direct exercise energy expenditure is much lower with HIT compared with aerobic exercise, the (potentially superior) reductions in fat mass following HIT have been hypothesised to be a result of either an increase in energy expenditure through a more prolonged EPOC and/or a reduction in energy intake through suppression of appetite (Boutcher 2011).…”
Section: Rehit May Affect Energy Balancementioning
confidence: 80%
See 3 more Smart Citations
“…Furthermore, we demonstrated that EPOC is significantly greater following 10 min of REHIT compared to 30 min of moderate intensity aerobic exercise. These findings are of importance as several previous studies have observed reductions in fat mass following HIT with some evidence for superior reductions compared with traditional aerobic training (Whyte et al 2010;Gillen et al 2013;Heydari et al 2012;Trapp et al 2008). Since direct exercise energy expenditure is much lower with HIT compared with aerobic exercise, the (potentially superior) reductions in fat mass following HIT have been hypothesised to be a result of either an increase in energy expenditure through a more prolonged EPOC and/or a reduction in energy intake through suppression of appetite (Boutcher 2011).…”
Section: Rehit May Affect Energy Balancementioning
confidence: 80%
“…As 'lack of time' has been identified as one of the main barriers to becoming and remaining physically active (Korkiakangas et al 2009;Reichert et al 2007), over the past decade research has focused on high-intensity interval training (HIT) as a timeefficient alternative to aerobic exercise . Although initial studies have convincingly demonstrated equal or better health benefits with various HIT protocols compared to much larger volumes of aerobic exercise (Gibala et al 2006;Shepherd et al 2013;Cocks et al 2013;Burgomaster et al 2008;Trapp et al 2008;Gillen et al 2013;Little et al 2010), these HIT protocols tend to be very strenuous and as such are unlikely to be adhered to by sedentary populations. Furthermore, most HIT protocols are not as time-efficient as sometimes claimed, with the total time per exercise session generally exceeding 20-30 minutes (Gibala et al 2006;Rakobowchuk et al 2008;Shepherd et al 2013;Cocks et al 2013;Burgomaster et al 2008;Trapp et al 2008;Gillen et al 2013;Little et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, considering the significance of intensity and duration of exercise training programs [32], HIIT programs have been identified as a fat controlling intervention [33]. The control of weight increase due to the high fat content of diet [34] compared to the stable aerobic activity, improvement in fat distribution and insulin with similar energy cost [35], has an effect on obesity. Regardless of the benefits of physical activities in improvement of obesity, there are inconsistent findings with regards to decrease in fat indices through participation in physical activities without calorie restriction.…”
Section: Introductionmentioning
confidence: 99%